Hubristic Start-up Founders – The Neglected Bright and Inevitable Dark Manifestations of Hubristic Leadership in New Venture Creation Processes - Janina Sundermeier; Martin Gersch; Jörg Freiling (Journal of Management Studies, 2020)
The hubris tradition of research has been criticized for limiting its scope by associating hubris predominantly with detrimental leadership behaviours. To counteract this bias, we provide a more nuanced exploration of hubris and consider both beneficial and detrimental manifestations of hubris in start-up founders' leadership behaviours. Our analysis, based on qualitative data from expert interviews and two case studies, indicates that, whilst hubristic start-up founders are likely to fail overall, they also excel in creating and communicating visionary scenarios, steering employees through critical situations, and extracting commitment from third parties. These under-researched `bright' manifestations of hubris allow start-up founders to lead their venture towards a stage, in which their visionary power and resilience become crucial prerequisites for economic progress. Our findings extend knowledge on hubristic leadership, offer new directions for the hubris tradition of research, and open up avenues for future research with a more balanced view of hubris.
Keywords: 650; entrepreneurial personality; hubris; leadership behaviours; start-up founders